Worsening Cardiac Function in a Patient with Friedreich’s Ataxia Secondary to Profound Hypothyroidism - Thrasher, Bradly J.; Whitham, Jennifer; Law, Jennifer (Experimental and Clinical Endocrinology & Diabetes Reports, 2018)
We present a case of declining cardiac function in a patient with Friedreich's Ataxia, however, her worsening cardiac function was not related to her chronic disease. Her declining cardiac function was associated with hypothyroidism that was initially overlooked. The purpose of this article is to remind physicians of the role that thyroid hormone has in cardiac function and overall health. Autoimmune hypothyroidism is a common condition, and physicians should consider screening thyroid function in any patient with poor or worsening cardiac function.
Keywords: Freidreich’s ataxia; pericardial effusion; hypothyroidism; levothyroxine